Hamstring injury patterns in professional male football (soccer): a systematic video analysis of 52 cases. Issue 3 (7th December 2021) - Gronwald, Thomas; Klein, Christian; Hoenig, Tim; Pietzonka, Micha; Bloch, Hendrik; Edouard, Pascal; Hollander, Karsten
Abstract : Objective: To closely describe the injury inciting events of acute hamstring injuries in professional male football (soccer) using systematic video analysis. Methods: Video footage from four seasons (2014–2019) of the two highest divisions in German male football was searched for moderate and severe (ie, time loss of >7 days) acute non-contact and indirect contact match hamstring injuries. Two raters independently categorised inciting events using a standardised procedure to determine specific injury patterns and kinematics. Results: 52 cases of hamstring injuries were included for specific pattern analysis. The pattern analysis revealed 25 sprint-related (48%) and 27 stretch-related hamstring injuries (52%). All sprint-related hamstring injuries occured during linear acceleration or high-speed running. Stretch-related hamstring injuries were connected with closed chain movements like braking or stopping with a lunging or landing action and open chain movements like kicking. The kinematic analysis of stretch-related injuries revealed a change of movement involving knee flexion to knee extension and a knee angle of <45° at the assumed injury frame in all open and closed chain movements. Biceps femoris was the most affected muscle (79%) of all included cases. Conclusion: Despite the variety of inciting events, rapid movements with high eccentric demands of the posterior thigh are likely the main hamstring injury mechanism. This study provides important data about how hamstring injuries occur in professional male football and supports the need for demand-specific multicomponent risk reduction programmes.